2010
DOI: 10.1080/13573320903461087
|View full text |Cite
|
Sign up to set email alerts
|

HPE and the moral governance of p/leisurable bodies

Abstract: Contemporary notions of good citizenship and proper living have become intimately related to the pursuit of good health. Consequently, modern states have devised programmes of education and training that endeavour to provide apprentice citizens with the knowledge, skills and attitudes required to enhance their own and others health and wellbeing. These strategies, deployed through institutions such as schools, contribute to the moral regulation of subjects, focusing as they do upon the moral and ethical practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…This research found that teachers continue to uncritically accept the dominant obesity and healthism discourses. This is despite findings by academics who challenge and call for teachers (such as health and physical educators) to examine their practices and curricula that reproduce social meanings for students that in turn perpetuate such negative body discourses (Alfrey & Brown, 2013;Burrows, Wright & McCormack, 2009;Cliff & Wright, 2010;Evans et al, 2008;Lee & Macdonald, 2010;McCuaig & Tinning, 2010;Quennerstedt & Ohman, 2014).…”
Section: Message Systemsmentioning
confidence: 95%
“…This research found that teachers continue to uncritically accept the dominant obesity and healthism discourses. This is despite findings by academics who challenge and call for teachers (such as health and physical educators) to examine their practices and curricula that reproduce social meanings for students that in turn perpetuate such negative body discourses (Alfrey & Brown, 2013;Burrows, Wright & McCormack, 2009;Cliff & Wright, 2010;Evans et al, 2008;Lee & Macdonald, 2010;McCuaig & Tinning, 2010;Quennerstedt & Ohman, 2014).…”
Section: Message Systemsmentioning
confidence: 95%
“…The purported positive correlation between sport and improved health is also often uncritically promoted through medico-scientific research, particularly in investigations related to the so-called obesity epidemic (Theberge, 2008;Zanker & Gard, 2008). In this body of research, sport gets lumped together with exercise and physical activity, connecting the pursuit of good health to "good citizenship" and "proper living" (Howell & Ingham, 2001;Ingham, 1985;McCuaig & Tinning, 2010). The common theme -either explicit or implicit -among these various scenarios is the link suggested to exist between sport and improvements to one's health.…”
Section: Please Scroll Down For Articlementioning
confidence: 98%
“…To this end, we preface our discussions regarding the current curriculum development process with a genealogical account of Queensland HPE curriculum reform, to demonstrate the shifting principled strategies, technologies, and practices deployed within and towards HPE to construct a particular subject: the active healthy citizen (McCuaig and Tinning 2010). As Rose (2000) notes, the genealogy of subjectification approach owes much of its theoretical underpinnings to Foucauldian theory and the 'problematizations through which being offers itself to be, necessarily, thought -and the practices on the basis of which these problematizations are formed' (Foucault 1990, 11).…”
Section: Problematising the Good Lifementioning
confidence: 99%